DIRECTED MOTIVATIONAL CURRENT (DMC) : A FUTURE RESEARCH AGENDA FOR INDONESIAN EFL TERTIARY STUDENTS - Sahril Nur; Aswin Abbas; Ali Syahban Amir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Abstract There is a growing interest in researching A Directed Motivational Current or DMC this current period. The interest arose considering that DMC is the newest, unique and phenomenal motivational piece that embodies and elicits very positive and powerful motivational experiences which is constructed individuals or groups to achieve worthy goals with incredible speed, included learning English as the second language (L2). A DMC qualitatively is different from the ongoing motivation of a good students, cause of is relatively short-term, highly intense burst of motivational energy and along with a specific way of a clearly defined destination. A DMC research was popularized less than a decade ago (Dörnyei, Ibrahim & Muir, 2015; Dörnyei, Muir & Ibrahim, 2014; Henry, Davydenko & Dörnyei, 2015; Muir & Dörnyei, 2013) that has been popular in every research conducted in several countries, including in Indonesia EFL tertiary students, although the number found is still small. We started by providing an overview of the structure of the DMC itself, the nature of DMC introducing by Dornyei, who stated that having the nature of DMC, experiences it, can trigger students in receiving their goal. The core dimensions, a foundation, as distinguishing from other motivation term are goal/vision orientedness, salient and facilitative structure and positive emotionality. In addition, the paths for future research in pedagogical reserach direction as an illustration to research on DMC theory also was described, where they might begin and the scope of the future research in the context of EFL students in Indonesian tertiary level. The last is to make DMC a future research agenda. This is to answer the challenges of researchers who summon experts to conduct further research related to DMC in L2, due to the lack of this research in the realm of foreign language learning. Keywords: directed motivational current/DMC, language learner motivation, Future agenda of DMC.